KAJIAN FERTIGASI PADA TANAMAN BAYAM (Amaranthus tricolor L.) DENGAN METODE TANAM HIDROPONIK (A Spinach Fertilization Study (Amaranthus tricolor L.) Using Hydroponic Cropping Method) - Haris Nawarisa; Sumono Sumono; Nazif Ichwan (Universitas Sumatera Utara, 2018)
ABSTRACT In the hydroponic system, the nutritional requirements is given along through irrigation that is known as fertigation. In fertigation the use of fertilizers can be arranged in quantities and concentrations corresponding to the needs of the plant during plant growth to obtain optimal results of good quality. This study was aimed to examine the fertilization of spinach (Amaranthus tricolor L.)using hydroponic cropping method. Research at screen house scale consisted of 2 treatments and 26 replicates, ie irrigation for 6 hours and watering for 8 hours. The parameters observed were the concentration of AB mixed nutrient solution, water discharge, wet weight and dry weight of plant, and economic analysis. The results showed that the concentration of AB mixed solution was 3.12% N, 0,0000003% P, and 3.76% K, the average initial water discharge for 6 hours was 7.013 x 10-4 l/s, irrigation for 8 hours was 5.260 x 10-4 l/s, and the final average water discharge for watering for 6 hours was 6.303 x 10-4 l/s, for irrigation for 8 hours was 4.683 x 10-4 l/s, the wet weight of spinach was plants ranged from 9.89 to 13.05 g and the dry weight of spinach plants was ranged from 0.76 to 1.31 g, and the economic analysis of the value of NPV with interest rate of 4.25% was Rp 2,261,255.6 this means the business is feasible to run. Keywords: Fertigation, Spinach, Hydroponics ABSTRAK Pada sistem hidroponik, kebutuhan nutrisi diberikan bersamaan dengan irigasi dikenal dengan istilah fertigasi. Pada fertigasi penggunaan pupuk dapat diatur dalam jumlah dan konsentrasi yang sesuai dengan kebutuhan dari tanaman selama pertumbuhan tanaman untuk memperoleh hasil yang optimal dengan kualitas baik. Penelitian ini bertujuan untuk mengkaji fertigasi pada tanaman bayam (Amaranthus tricolor L.) dengan metode tanam hidroponik. Penelitian dalam skala rumah kasa terdiri dari 2 perlakuan dan 26 ulangan, yaitu pengairan selama 6 jam dan pengairan selama 8 jam. Parameter yang diamati meliputi konsentrasi larutan nutrisi AB mix, debit air, bobot basah dan bobot kering tanaman, dan analisis ekonomi. Hasil penelitian menunjukkan konsentrasi larutan AB mix yakni 3,12 % N, 0,0000003 % P, dan 3,76 % K, debit air awal rata-rata untuk pengairan selama 6 jam yakni 7,013 x 10-4 l/s, untuk pengairan selama 8 jam yakni 5,260 x 10-4 l/s, dan debit air akhir rata-rata untuk pengairan selama 6 jam yakni 6,303 x 10-4 l/s, untuk pengairan selama 8 jam yakni 4,683 x 10-4 l/s, bobot basah tanaman bayam berkisar 9,89 – 13,05 g dan bobot kering tanaman bayam berkisar 0,76 – 1,31 g, dan analisis ekonomi dari besarnya nilai NPV dengan suku bunga 4,25 % yakni Rp 2.261.255,6 yang berarti usaha ini layak dijalankan. Kata Kunci: Bayam, Fertigasi, Hidroponik